A Doctor's Worth: Bonus Criteria and the Gender Pay Gap among American Physicians. (March 2016) - Roth, Louise Marie
Pay-for-performance (P4P) programs, based on productivity, patient satisfaction, quality of care, efficiency profiling, or unspecified criteria have become popular in American medicine. Theoretically, such programs hold the potential to narrow the gender pay gap among physicians by employing what are arguably neutral, meritocratic criteria. Such criteria are often unspecified in prior analyses but in reality may include a host of indicators, including objective features of performance, dimensions that entail a high degree of discretion, and gendered aspects, such as masculine competence (i.e., intelligence, confidence, efficiency, and decisiveness) or feminine warmth (i.e., kindness, trustworthiness, sympathy, and selflessness). Using data from four waves of the Community Tracking Study (CTS) Physician Surveys, I analyze the effects of such unique P4P criteria on the gender pay gaps among physicians. Most notable among findings is more pronounced gender inequality when criteria are unspecified as opposed to being based on productivity . No effect is found when P4P centers on warmer patient satisfaction criteria. I conclude by discussing how and why P4P schemes may reduce but also exacerbate gender inequalities in pay.